Cambios de gobierno en la vida de un botánico mexicano: Maximino Martínez (1888-1964) - Cuevas Cardona, Consuelo; López Ramírez, Carmen (El Colegio de México, A.C., 2009)
Maximino Martínez was an elementary school teacher who also came to be an acknowledged botanist. Basically self-taught, he began his professional development in 1914, at the National Museum of Natural History, and went on in the Department of Biological Studies from 1915 to 1929. His biography reveals the effect of factors unconnected to science, such as government  changes and social movements, on the life of a scientist  during this period.